A new Holocene relative sea-level curve for Terra Nova Bay, Antarctica - BARONI, CARLO; Hall B. L. (Journal of Quaternary Science, 2004)
More than 100 radiocarbon dates of penguin guano and remains, shell and seal skin afford ages for raised beaches adjacent to Terra Nova Bay, Antarctica. These dates permit construction of a new relative sea-level curve that bears on the timing of deglaciation. Recession of the Ross Sea ice-sheet grounding line from Terra Nova Bay occurred no earlier than 7200 14C yr (8000 cal. yr) BP. Retreat along the Victoria Land coast may have been rapid, possibly contributing to eustatic sea-level rise centred at ca. 7600 cal. yr BP. The presence of a significant amount of ice remaining in the Ross Sea Embayment in Holocene time lessens the chance that Antarctica contributed significantly to meltwater pulse 1A several thousand years earlier. © 2004 John Wiley and Sons, Ltd.